2011
DOI: 10.4310/ajm.2011.v15.n4.a5
|View full text |Cite
|
Sign up to set email alerts
|

P. D. E.'s Which Imply the Penrose Conjecture

Abstract: Abstract. In this paper, we show how to reduce the Penrose conjecture to the known Riemannian Penrose inequality case whenever certain geometrically motivated systems of equations can be solved. Whether or not these special systems of equations have general existence theories is therefore an important open problem. The key tool in our method is the derivation of a new identity which we call the generalized Schoen-Yau identity, which is of independent interest. Using a generalized Jang equation, we use this ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
130
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(133 citation statements)
references
References 35 publications
(79 reference statements)
3
130
0
Order By: Relevance
“…The existence, regularity, and blow-up behavior for solutions of the generalized Jang equation was studied in [28], and discussed in [7,8]. Moreover, in [14] it was shown that the new data possess the desired asymptotics and that the mass is preserved up to a contribution from the warping factor.…”
Section: The Penrose Inequalitymentioning
confidence: 99%
See 4 more Smart Citations
“…The existence, regularity, and blow-up behavior for solutions of the generalized Jang equation was studied in [28], and discussed in [7,8]. Moreover, in [14] it was shown that the new data possess the desired asymptotics and that the mass is preserved up to a contribution from the warping factor.…”
Section: The Penrose Inequalitymentioning
confidence: 99%
“…The purpose of the generalized Jang equation is to impart a desired lower bound for the scalar curvature of g 1 . Namely, as is shown in [7,8] we have…”
Section: The Positive Mass Theoremmentioning
confidence: 99%
See 3 more Smart Citations